Air pollutant emissions by anthropogenic combustion processes in Lagos, Nigeria - Bamidele Sunday Fakinle; Ebenezer Leke Odekanle; Abiodun Paul Olalekan; Henry Egbonyi Ije; Daniel Olawale Oke; Jacob Ademola Sonibare (Cogent Engineering, 2020)
As part of research efforts to investigate the contribution of various anthropogenic activities to local atmospheric pollution load across Nigeria, the study investigated emission of air pollutants from the combustion processes in Lagos mega city. Solid wastes, consumption of fuel wood, and petroleum products were identified as major materials being combusted in Lagos and these materials were quantified based on the information in literature. Annual emissions from the combustion of the quantified materials were estimated using emission factor approach. The total estimated annual contribution of anthropogenic combustion processes to atmospheric loading of PM10, CO, SO2, NOx and VOC were 188.49, 5920.97, 11.24, 348.88 and 4.14 kt/annum, respectively. Emissions from the combustion of solid waste/biomass were identified as a major source of criteria air pollutants in the city because, about 67.5% and 82% of the estimated CO and PM10 emissions, respectively, were generated from the combustion of solid waste/biomass. Also, 81%, 57% and 32% of NOx, SO2 and CO emissions respectively were found to have emanated from combustion of kerosene. These elevated emission levels can be said to have potential impacts on ambient air quality of the study area. The study concluded that immediate mitigating action to reduce release of pollutants from combustion processes should be put in place.